Lone Wolf McQuade [videorecording (DVD)] - Nelson, B. J.; Norris, Chuck, 1940-; Carradine, David; Carrera, Barbara; Kennedy, Leon Isaac; Jones, L. Q., 1927-2022 (MGM DVD., 2012)
A renegade Texas Ranger tries to give his new sidekick the slip and becomes involved in a violent battle against a gun runner in this action film featuring martial arts battles.